(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Concrete is a composite material comprised of coarse rock connected along with liquid concrete that solidifies over the long run and is viewed as the foundation of the structure business. Since the substantial business polishes off 1.5 billion tons of concrete, 900 million liters of water, and 9 million tons of sand and water every year, there is a need to foster an option eco-accommodating material that will keep our normal assets from being depleted. The author of this article discusses the materials used in concrete preparation, as well as their kinds and testing. The primary goal of sustainable development is to discover alternative materials that will reduce the negative effects of the concrete industry on the environment while also contributing to natural resource preservation. The purpose of this article is to describe the concrete preparation process as well as the negative effects of the elements used in it.